2018
DOI: 10.1080/03650340.2018.1461211
|View full text |Cite
|
Sign up to set email alerts
|

Performance of common buckwheat (Fagopyrum esculentumM.) in response to row spacing under ridge and furrow cropping systems in a semiarid region of China

Abstract: Increasing atmospheric carbon dioxide concentration (CO 2 ) is an important component of global climate change that will have a significant impact on the productivity of crop plants. In recent years, growth and yield of agricultural crop plants have been shown to increase with elevated CO 2 (EC) and have enticed considerable interest due to variation in the response of crop plants. In this study, comparative response of two mung bean cultivars (HUM-2 and HUM-6) was evaluated against EC at different growth stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The selection of buckwheat genotypes suitable for further breeding requires the characterization and evaluation of genetic resources [48]. Significant differences among years and genotypes were observed for morphological traits [49,50]. Due to the great nutritional value of buckwheat, certification should be worked on as well as branding buckwheat products, because buckwheat has a significant place in programs of integral and organic production systems.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of buckwheat genotypes suitable for further breeding requires the characterization and evaluation of genetic resources [48]. Significant differences among years and genotypes were observed for morphological traits [49,50]. Due to the great nutritional value of buckwheat, certification should be worked on as well as branding buckwheat products, because buckwheat has a significant place in programs of integral and organic production systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the planting pattern of P 1 (50 cm mounds with 2 planting rows and the intervals of 20 cm), due to high contest of single-bush plants, generative stage will begin earlier and the maximum number of flowers may be achieved while harvesting the flowers to measure the rutin percent. In a study on how to grow buckwheat, they reported that planting two rows in dry and semi-arid areas were the best way to optimally consume soil nitrogen [37]. In relation to nitrogen treatment, as reported, nutrients are one of the most important factors affecting the amount of active ingredient.…”
Section: Flower Rutin Percent (%)mentioning
confidence: 96%
“…It was reported that the use of 35 kg of nitrogen per hectare yields the highest rutin yield per grain [17]. The association between optimal nitrogen consumption with plant density and two-row planting arrangement in buckwheat has been reported [37,62]. Honermier and Wagenbreth (2000) have seen the increase of rutin percent as 18 to 29 % in the buckwheat using 0 to 90 Kg ha -1 of nitrogen [47].…”
Section: Grain Rutin Percent (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the irregular shape of buckwheat seeds and the difficulty of mechanized seeding, the yield and production efficiency of buckwheat are low [5], which severely restricts the development of the buckwheat industry [6]. At present, there are three main seeding methods for buckwheat, including drill seeding, broadcast seeding and hole seeding [7,8]. Compared with drill seeding and broadcast seeding, hole seeding planting has the advantages of strong seedling breaking ability, fast seedling emergence, and high average yield [9], which meets the needs of precision agriculture operations.…”
Section: Introductionmentioning
confidence: 99%